AN ANALYSIS ON THE STUDENTS' CHALLENGES FACED IN WRITING PROCEDURE TEXTS AT BUDI MURNI 1 - Cut Fadillah Irawaty; Fachri Yunanda; Anggi Mida Roma Simalango; Widya Lorenza Simanullang; Bambang Nur Alamsyah Lubis (Jurnal Basataka (JBT), 2024)
Writing is a crucial component of language acquisition. This method may be intricate,particularly for non-native speakers. This study aims to identify the challenges encountered by eleventhh-grade students in composing procedure texts and to ascertain the obstacles contributing to these issues. This approach constitutes qualitative research. The subjects of this study were 21 eleventh-grade pupils. The findings indicated that the data were analyzed with a rubric analytical scale by brown (2007). The results indicated that 19% of students achieved a very good level, 23.80% attained a good level, 33.33% reached a medium level, and 23.80% were classified at a poor level. Therefore, we label 28.5% of students as having poor language features. This means that language features are the most difficult area for eleventh-grade students at SMA Budi Murni 1 with 28.5% of students being at the poor level.